Penyuluhan Gizi Seimbang Pada Ibu Hamil dan Persiapan Laktasi - I, Isnaeny; R, Rika (Yayasan Daarul Huda Kruengmane, 2025)
Balanced nutrition is a daily food composition that contains nutrients in types and amounts that are in accordance with the body's needs, by considering the principles of diversity or variety of foods, physical activity, cleanliness, and ideal body weight. A pregnant woman must have good nutritional status and consume a variety of foods both in proportion and quantity. Pregnant women must consume more food because they must meet the nutritional needs for themselves and for the growth and development of their fetus/baby. If the mother's daily food does not contain enough nutrients, the fetus or baby will take the supplies in the mother's body. Based on this, we will carry out community service to provide an understanding of increasing Knowledge of Balanced Nutrition in pregnant women and Lactation preparation. The purpose of this community service is to increase the knowledge of pregnant women about the Importance of Balanced Nutrition during Pregnancy and preparation for lactation in the Bontonompo I Health Center Working Area, South Bontonompo District, Gowa Regency. This counseling is expected to provide provisions to the community, especially pregnant women, to be able to protect themselves and their families against stunting and as early as possible pregnant women know about exclusive breastfeeding so that later they can provide exclusive breastfeeding to their babies.Balanced nutrition is a daily food composition that contains nutrients in types and amounts that are in accordance with the body's needs, by considering the principles of diversity or variety of foods, physical activity, cleanliness, and ideal body weight. A pregnant woman must have good nutritional status and consume a variety of foods both in proportion and quantity. Pregnant women must consume more food because they must meet the nutritional needs for themselves and for the growth and development of their fetus/baby. If the mother's daily food does not contain enough nutrients, the fetus or baby will take the supplies in the mother's body. Based on this, we will carry out community service to provide an understanding of increasing Knowledge of Balanced Nutrition in pregnant women and Lactation preparation. The purpose of this community service is to increase the knowledge of pregnant women about the Importance of Balanced Nutrition during Pregnancy and preparation for lactation in the Bontonompo I Health Center Working Area, South Bontonompo District, Gowa Regency. This counseling is expected to provide provisions to the community, especially pregnant women, to be able to protect themselves and their families against stunting and as early as possible pregnant women know about exclusive breastfeeding so that later they can provide exclusive breastfeeding to their babies.